(untitled) (Research, Society and Development, 2020)
Leaf anatomy as a subsidy to the taxonomy of the genus Camarea St.-Hil (Malpighiaceae). Camarea is endemic in Brazil and is part of the Gaudichaudieae tribe, which has morphological characteristics, such as its kleistogamic flowers and the reduction of structures in casmogamic flowers, however the existing morphological characters are still not enough to solve problems related to the genus. analyze. Thus, the objective was to describe the morphology of six species of the Camarea in search of characters that can assist in the delimitation of species. The species were obtained from herbariums, cut freehand, stained and compared with each other. In this article, it is possible to observe useful characters to distinguish species such as: morphology of the leaf glands, contour of the petiole and the main vein, stratification of the epidermis and type of mesophyll. The results obtained helped to distinguish the analyzed species and brought new data to the clade, such characteristics can help in future taxonomic and phylogenetic studies of the group, making clear the importance of anatomy as a tool for taxonomy.